2020
DOI: 10.3390/ijms21134598
|View full text |Cite
|
Sign up to set email alerts
|

Sex Chromosomes Are Severely Disrupted in Gastric Cancer Cell Lines

Abstract: Sex has not received enough attention as an important biological variable in basic research, even though the sex of cells often affects cell proliferation, differentiation, apoptosis, and response to stimulation. Knowing and considering the sex of cells used in basic research is essential as preclinical and clinical studies are planned based on basic research results. Cell lines derived from tumor have been widely used for proof-of-concept experiments. However, cell lines may have limitations in testing the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…However, cell lines tend to continuously mutate as the passage number increases during cell culture. A previous study indicated that a loss of Y chromosome accompanied with X chromosome duplication in three of six male gastric cancer cell lines tested 27 . Also two of six female gastric cancer cell lines showed a loss of one X chromosome.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, cell lines tend to continuously mutate as the passage number increases during cell culture. A previous study indicated that a loss of Y chromosome accompanied with X chromosome duplication in three of six male gastric cancer cell lines tested 27 . Also two of six female gastric cancer cell lines showed a loss of one X chromosome.…”
Section: Discussionmentioning
confidence: 94%
“…A previous study indicated that a loss of Y chromosome accompanied with X chromosome duplication in three of six male gastric cancer cell lines tested. 27 Also two of six female gastric cancer cell lines showed a loss of one X chromosome. These results indicate that cells isolated from male or female tissues may not fully represent the sex characteristics of the donors especially when those cells are immortalized.…”
Section: F I G U R Ementioning
confidence: 98%
“…The clean reads were then mapped to the human genome (GRCh38_Ensembl104) using the Hisat2 [40]. HTseq was used to obtain the gene counts, and the FPKM method was used to determine the gene expression [41].…”
Section: Rna Sequencingmentioning
confidence: 99%